KARAKTERISASI SIFAT FISIK MINYAK Eucalyptus DARI Eucalyptus grandis SECARA ENZIMATIS - Muhammad Taufik; Ananta Akram (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2020)
Research on the characterization of the physical properties of Eucalyptus oil from Eucalyptus grandis enzimatically using achatina fulica snail enzymes has been carried out to obtain a method suitable for volatile essential oils. This study uses the (RAL) method using two factorial. Factor 1 is the particle size consisting of 4 treatment vis, U1= 20 mesh, U2= 40 mesh, U3= 60 mesh, U4 80 mesh. Factor 2 is maceration time which consis of 4 treatments viz, M1= 2 days, M2= 3 days, M3= 4 days, M4= 5 days. The parameters observed were yield, specific gravity, refractive indeks, and aroma. From the results of the statistical analysis on each maceration time parameter gives a very significant effect (p<0,01) on the yield value, specific gravity, refractive index, and scent. Particle size gives a very significant effect (p<0,01) on yield value, specific gravity, refractive indeks, and scent.